The determinants of China’s IPO underpricing and short-run post-IPO performance - xue, wang (2019)
IPO (initial public offering) underpricing exists across the world, and there are a large number of studies about it. There is also considerable literature investigating China’s IPO underpricing. Due to the changing policies, the rapid development of China’s economy and capital market, and the increasing international cooperation, the different views of point in how to interpret China’s IPO underpricing appear one after another in recent years. From these various theories, we can get a glimpse of the intricate situation on China’s IPO underpricing. The majority of extant literature document China’s IPO underpricing before 2014. However, the degree of China’s IPO underpricing has significantly changed since the implementation of price limits on 13th Dec 2013. Hence, in this paper, the situation of IPO underpricing after 13th Dec 2013 has been included and explored. Specifically, this study sheds light on the determinants of IPO underpricing based on the existing mainstream theories of IPO underpricing from 19th June 2006 to 6th August 2018(leaving 7th August 2018 to 1st August 2019 for examining the short-run post-IPO performance). In addition to this, the influence of the US stock market on China’s IPO underpricing is examined considering the American significant international influence, enhanced international economic integration and the boom of electronic information technology. Moreover, the trade war between America and China has caught the eye of the whole world, which prompts it is more interesting and meaningful to probe into the correlation between the fluctuation of the US stock market and China’s IPO underpricing. To figure out the relation between them, the volatility of the S&P 500 index price prior to IPOs as a proxy has been incorporated in our regression model, and a statistically significant relationship is presented in the model, implying the integration between China’s IPO market and the US stock market to a certain extent. From investors’ standpoint, they are concerned about the determinants of IPO underpricing, as well as the aftermarket performance following IPO. Retail investors account for the majority of participants in China’s stock market, and most of them invest in stocks for speculation purposes according to the extant literature (Song, Tan and Yi, 2014). In the interest of them, the IPO aftermarket within 240 trading days performance has been discussed in our paper, and investment advice has been given based on our study.